The Silent Saboteur: Chronic Refractory Erythema Nodosum Leprosum Perpetuated by Neglected Odontogenic Foci in a Post-RFT Borderline Lepromatous Patient - Antonio Orson Ongkowidjojo; Luh Made Mas Rusyati; Stefanus Soewito Sutanto (HM Publisher, 2026)
Background: Erythema nodosum leprosum (ENL) is a severe, immune-complex mediated complication of lepromatous leprosy that can manifest before, during, or after multidrug therapy (MDT). While the primary etiology involves the release of Mycobacterium leprae antigens, the chronicity of ENL is frequently driven by secondary, often occult, triggers. Focal infections, particularly of odontogenic origin, are frequently overlooked in standard dermatological assessments, leading to refractory clinical courses. Case presentation: We report the case of a 32-year-old male with a history of borderline lepromatous (BL) leprosy who had achieved release from treatment (RFT). The patient presented with severe, chronic, and recurrent ENL characterized by painful erythematous nodules, high-grade fever, and acute neuritis, occurring more than one year post-RFT. Laboratory evaluation revealed significant inflammatory markers, including a C-Reactive Protein level of 172.7 mg/L and leukocytosis. Crucially, intraoral examination identified neglected chronic dental caries (gangrene radix) and generalized periodontal inflammation. Despite medical advice, the patient refused dental intervention. The reactional state was managed with a combination of intravenous methylprednisolone and high-dose oral clofazimine. While cutaneous symptoms improved, the persistence of the focal infection poses a substantial risk for further recurrence. Conclusion: This case highlights the critical and often underestimated role of odontogenic focal infections as perpetuating factors in chronic ENL. It underscores the necessity for a multidisciplinary approach integrating dentistry and dermatology. We propose that recalcitrant ENL in post-RFT patients should trigger mandatory screening for occult dental infections to disrupt the cycle of systemic inflammation.